2013
DOI: 10.1111/ajo.12042
|View full text |Cite
|
Sign up to set email alerts
|

A threefold increase in gestational diabetes over two years: Review of screening practices and pregnancy outcomes in Indigenous women of Cape York, Australia

Abstract: The rate of GDM tripled after implementation of universal testing. Outcomes improved. There is still need for improvement in testing and follow-up practices in relation to DIP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 18 publications
1
38
1
Order By: Relevance
“…However, the rates of 14 % postpartum screening among Indigenous women by 6 months postpartum observed in our study, were significantly lower than the rates of 38 % by 6 weeks postpartum reported in Canada in 1998 [31], and 37 % reported among Maori and non-Maori women more recently in New Zealand [32]. The only other study to date to report postpartum diabetes screening among Indigenous women in Australia, also in Far North Queensland during the same study period, noted that OGTTs were performed in 1/6 (16.6 %) Indigenous women diagnosed with gestational diabetes in 2006, and 6/19 (31.6 %) Indigenous women diagnosed with gestational diabetes in 2008 [34]. The variation from our study is likely due to small numbers.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…However, the rates of 14 % postpartum screening among Indigenous women by 6 months postpartum observed in our study, were significantly lower than the rates of 38 % by 6 weeks postpartum reported in Canada in 1998 [31], and 37 % reported among Maori and non-Maori women more recently in New Zealand [32]. The only other study to date to report postpartum diabetes screening among Indigenous women in Australia, also in Far North Queensland during the same study period, noted that OGTTs were performed in 1/6 (16.6 %) Indigenous women diagnosed with gestational diabetes in 2006, and 6/19 (31.6 %) Indigenous women diagnosed with gestational diabetes in 2008 [34]. The variation from our study is likely due to small numbers.…”
Section: Discussionmentioning
confidence: 94%
“…Low rates of postpartum screening have been reported among non-Indigenous women in Australia [29] and internationally [30]; with particularly low rates reported among Indigenous women in similar high income countries, including Canada [31], and New Zealand [32,33]. One small study recently reported low rates of postpartum screening among Indigenous women in Far North Queensland [34]. This study is timely with recent changes to national diabetes screening guidelines [16], which have particular implications for Indigenous women.…”
Section: Introductionmentioning
confidence: 86%
“…Regarding concerns related to workload and workforce issues, Australian publications have predicted and indeed shown an increase of between 20 and 30% 9,10 in GDM cases with these new criteria, whilst others have shown lesser increases (12.5 and 20%) and indeed no significant change in prevalence in Indigenous women in Cape York. [11][12][13] Regarding the concern about first trimester GDM diagnosis, a recent statement by IADPSG 14 recommends against the use of a fasting glucose threshold ≥ 5.1 mmol/L for GDM diagnosis in early pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, changing testing strategy among Aboriginals in Australia from selective risk-factor-based screening to universal screening resulted in an increase of 40% in prevalence of GDM [25]. Actually, FIGO recommends that all pregnant women are tested for GDM using a 1-step procedure [20].…”
Section: Discussionmentioning
confidence: 99%